Development of "Didik Inklusif" E-Learning as an Educational Platform for Caregivers on Sex Education for Children with Special Needs - Nur Azizah,; Ratih Muharina,; Mujtahid, Muhammad Fachrul Hasan (Jurnal Pendidikan Bitara UPSI, 2025)
Sex education for children with special educational needs (SEN) is still often considered taboo. Many people assume that they do not need sex education because of the assumption that children with SEN do not have an understanding or need for this aspect. In addition, many caregivers have difficulty in teaching it due to limited understanding of the concept, lack of knowledge about the right method, and restricted access to learning resources or opportunities. As a result, children with SEN are at higher risk of becoming victims or perpetrators of sexual abuse. This lack of accessibility becomes the foundation of our research, highlighting the need for e-learning as a solution compared to other methods. This study aims to develop Didik Inklusif e-learning as a learning platform for caregivers on sex education for children with SEN, using the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) approach. The research involved a sample of 60 caregivers. The results indicate that 88.3% of caregivers expressed a high interest in using e-learning for sex education. Didik Inklusif answers this need by providing two types of classes namely Web Class and Live Class. In addition, Inclusive Education provides counseling services for caregivers in need and a community forum for sharing experiences and learning. Caregivers need the e-learning Didik Inklusif platform, which has a positive impact by providing a space for them to understand and implement sexual education for children with SEN.